Spiritual care training and the GP curriculum: where to now?. Issue 4 (4th July 2019) - Appleby, Alistair; Swinton, John; Wilson, Philip
ABSTRACT: This article examines the place of spirituality in medical education, with special reference to primary care. It highlights evidence of current discrepancies and problems with spiritual care in general practice, demonstrating that GPs do not have a common approach or set of competencies. The authors illuminate the fact that medical education teaches spirituality sporadically and largely through optional and non-embedded learning. This and the general paradigm and culture of medical education may actually impair doctors' ability to understand spirituality and integrate this in practice. The authors critique philosophical limitations in the Royal College of GPs' curriculum statements on spirituality and foreground more general problems with the current philosophy of science on which primary care is based. Consideration is given to retracting or reducing claims to address spirituality in primary care before solutions to these issues are put forward. Potential solutions proposed include a shift to a broader philosophical framework, such as "critical realism", and the use of alternative learning approaches such as transformational learning.